Dinamika Teknologi Kecakapan Hidup Sebagai Sinergi Literasi dalam Mengembangkan Writerpreneur di Forum Lingkar Pena - Intan Elok Okti Wardani; Dinda Triana Cindi; Mailawati (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The speed and up-to-dateness of communication and information have become essential demands in the era of Industry 4.0, particularly in the transformative aspect of literacy. In the rapid development of technology and information, there is a significant impact on the social fabric of society. Amidst the onslaught of passive technology, Forum Lingkar Pena advocates for awareness in developing literacy as a financial resource. Furthermore, the technology of life skills plays a central role in fostering writerpreneurs as part of the synergy of literacy. This research examines how technology engages life skills literacy as the core source of success for the writing profession in Forum Lingkar Pena and the literary layers of society. The research results rely on technology as a digital medium that enhances the productivity and relevance of writerpreneurs and disseminates literacy collaborations with grace on social media.